Becoming smart: exploring tourism suppliers’ perspectives on smart tourism destination engagement - Johnson, Abbie-Gayle (2021)
This thesis examines suppliers’ perspectives on engagement in smart destinations. Research on technologies in tourism follows a long-held tradition of lacking diverse theorisation and this has influenced knowledge development of smart tourism, which continue to draw on narrow perspectives of engagement. In order to provide a more holistic understanding of engagement in smart tourism, a collaborative approach was applied to this thesis. Power was identified as not being extensively discussed in tourism collaboration and smart tourism research, which is necessary for exploring smart contexts. This thesis applies Michel Foucault’s ideas on power, namely discourses and governmentality. This was done in order to unravel power relations and their effects on multiple individual suppliers in a destination that facilitates a participatory, bottom-up approach. This move can aid in understanding challenges experienced by suppliers within a smart context. The aim of this research is to examine suppliers’ perspectives on engaging in smart destinations, which is achieved through the following objectives: to understand the rationale for developing smart tourism, examine how smart tourism was developed, explore perceptions on the factors that influence engagement, examine supplier engagement through an analysis of discourses and governmentality. Methodologically, the research design employs a case study approach to Ljubljana, Slovenia, a 2019 and 2020 European Capital of Smart Tourism. Data collection focused on online material, printed documents and semi-structured interviews with suppliers, which are analysed using thematic and Foucauldian discourse analyses.